Modeling Human Mobility by Train on the Spread of COVID-19 in East Java Province Using Distance-Decay PageRank Algorithm - Rizha Al-Fajri; Medria Kusuma Dewi Hardhienata; Yeni Herdiyeni (Universitas Ahmad Dahlan, 2023)
Since early 2020, the world has been dealing with the COVID-19 outbreak. A person who has been infected with COVID-19 has the potential to transmit the virus to others. This study aims to model human mobility by train using the spatial network in East Java Province. This research examines the relationship between human mobility by train and the spread of COVID-19 in East Java Province. The spatial network is formed based on train stations and train trips, and the model was created using the Distance-decay PageRank algorithm. This research has modeled human mobility using the train in East Java Province. The result shows that human mobility by train is highly correlated with the spread of COVID-19 in East Java Province, with a correlation coefficient of 0.7 (r = 0.7).Since early 2020, the world has been dealing with the COVID-19 outbreak. A person who has been infected with COVID-19 has the potential to transmit the virus to others. This study aims to model human mobility by train using the spatial network in East Java Province. This research examines the relationship between human mobility by train and the spread of COVID-19 in East Java Province. The spatial network is formed based on train stations and train trips, and the model was created using the Distance-decay PageRank algorithm. This research has modeled human mobility using the train in East Java Province. The result shows that human mobility by train is highly correlated with the spread of COVID-19 in East Java Province, with a correlation coefficient of 0.7 ( = 0.7).